Sustainability in a Global Circular Economy: An Integrated Modeling Perspective - Hanumante, Neeraj C.; Shastri, Yogendra; Hoadley, Andrew (Frontiers in Chemical Engineering, 2020)
One of the UN Sustainability Goals is sustainable production and consumption. Global adoption of the Circular Economy (CE) is considered one of the critical methods of achieving this goal. Most of the studies in the field of CE investigate the economic benefits through material savings. The question of how CE, when adopted on a global level, can influence sustainability has been largely unexplored. We seek to examine the research into this question from an integrated perspective. A study looking into the systemic influences of the CE establishes its benefits. However, it also brings out the adverse ecological effects of very aggressive adoption of CE. Another study examines the role of consumer price sensitivity regarding CE in global sustainability. It suggests that though economic incentives can contribute to CE adoption, controlling the overall consumption growth rate is a more potent way of achieving sustainability. The stakeholders like the international organisations, multinational corporations, sustainability researchers and the public at large may find these insights helpful. This utility is discussed; along with the limitations and avenues for future research from these studies. To conclude, the importance of integrated modelling studies for CE is underlined through this article.